Growth of Bertholletia excelsa Bonpl. (Brazil nut) in Amazonia thirty years after bauxite mining - Salomão, Rafael de Paiva; Santana, Antônio Cordeiro de; Júnior, Silvio Brienza; Rosa, Nélson de Araújo; Precinoto, Raíza Salomão (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Bertholletia excelsa is a species widely distributed across Amazonia tested and recommended in the recovery of areas degraded by mining activity. In 1984, in an area under forest restoration within the Saracá-Taquera National Forest, a 19.4 ha reforestation patch was implemented with Brazil nuts seedlings planted along with those of 66 other species. We monitored the diameter growth of 416 Brazil nut trees over a ten-year period. The mean diameters observed for each time period were 19.2 ± 10.0 cm, 21.1 ± 10.7 cm, 23.2 ± 11.4 cm, 24.9 ± 11.9 cm and 28.2 ± 12.7 cm at 20, 22, 24, 26 and 30 years of age respectively. Growth increments were significant analyzed time periods. Mean height at 20 years was 15.6 ± 4.8 m (0.78 m yr-1). The Mean Annual Increment (MAI) of the diameter at breast height (DBH) was almost constant in all monitored periods (0.96 cm yr-1). A geometric growth rate model for diameter growth was proposed (R² = 0.99). Eighteen trees of 30 years of age were selected to serve as seed-producing trees for seedling production and for annual forest restoration areas planting as they show an annual increment of 2 cm in DBH.